Primary Leiomyosarcoma of the inferior vena cava – radical resection and vaskular reconstruction – case report - Petrovic, Ognjen; Srđan; Djurisic, Igor; Kocic, Milan; Babic, Andjela; Jokic, Vladimir; Pejnovic, Luka; Vucic, Nikola; Gacic, Stefan; Rajacic, Lila (Medical Research, 2024)
Introduction: Sarcomas are rare tumors that account for less than 1% of malignant tumors in adults. Primary leiomyosarcoma of the inferior vena cava is a very rare tumor with an incidence of <1/100,000 of all malignant diseases in adults. This paper presents the case of a woman with leiomyosarcoma of the inferior vena cava who underwent radical tumor resection with vascular reconstruction. Case report: A 71-year-old woman went to the doctor because of painless hematuria. As part of the diagnostic evaluation, in addition to US and CT examination of the abdomen, CT angiography with 3D reconstruction was performed. The conclusion of the radiologist was that the described tumor mass first corresponds to a primary leiomyosarcoma of the inferior vena cava that propagated laterally into the lumen of the left renal vein, while the right renal artery was infiltrated by the tumor. The patient was presented to the multidisciplinary team at the Institute for Oncology and Radiology of Serbia, which decided for operative treatment. The tumor was completely removed en bloc with the right kidney, right suprarenal gland and the confluence of the left renal vein into the inferior vena cava. The inferior vena cava was reconstructed with a graft with end-end anastomosis, while the left renal vein was implanted in the graft with end-side anastomosis. The patients postoperative course went well and she was discharged from the hospital on the VIII postoperative day. Conclusion: Leiomyosarcoma of the inferior vena cava is an extremely rare tumor. Surgical resection of the tumor and the involved blood vessel with negative resection margins is the only therapeutic option that improves survival. Very often with complicated vascular reconstructions, surgery also includes multivisceral resections, in order to achieve the best possible therapeutic effect.